Pemilihan Job Sheet Berbasis Assesment Checklist Sebagai Metode Pembelajaran Mata Kuliah Ilmu Ukur Tanah Untuk Meningkatkan Motivasi Mahasiswa Pendidikan Teknik Bangunan - Adilla Izmi Pratiwi (Universitas 45 Surabaya, 2023)
In the world of education, it is natural for researchers and teachers to innovate in the use of learning methods for students. One method that is often used is the Assessment Checklist-based Job Sheet. In line with the previous explanation, the purpose of this study was to see the feasibility of Job Sheet Based on Assessment Checklist as a Learning Method for Land Measurement Science Course. The method used in this research is a systematic literature review based on related research journals within the last five years. The results showed that the Assessment Checklist method is feasible to use in learning Land Measurement Science courses. The method can be an innovation that follows the times and with the help of pictures, tables and clear instructions can make it easier for students to understand learning materials.